2021
DOI: 10.3390/ijerph18136977
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Experiences of the COVID-19 Pandemic amongst Frontline Nurses and Their Relatives in France in Six Paradoxes: A Qualitative Study

Abstract: Due to their frontline position to fight the coronavirus disease 2019 (COVID-19), the professional and personal life of nurses was severely disrupted. To understand and describe their lived experiences and perceptions during the pandemic’s first wave in France, we interviewed 49 nurses, including 16 nursing students, and 48 of their family members from June to July 2020. Using a purposeful sampling, the semi-structured interviews were scripted according to Abric’s method with probing questions. The interview a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…It is difficult for nurses to find themselves in this new reality, taking into account the speed with which the disease is spreading, an insufficient time to prepare for a record number of seriously ill patients, the high mortality rate, everyday work in personal protective equipment, unpredictability of events, loss of control, sense of helplessness, and the fear accompanying everyday work routines. These are just some of the reasons why nurses’ work is extremely vulnerable to stress and its effects during the COVID-19 pandemic [ 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult for nurses to find themselves in this new reality, taking into account the speed with which the disease is spreading, an insufficient time to prepare for a record number of seriously ill patients, the high mortality rate, everyday work in personal protective equipment, unpredictability of events, loss of control, sense of helplessness, and the fear accompanying everyday work routines. These are just some of the reasons why nurses’ work is extremely vulnerable to stress and its effects during the COVID-19 pandemic [ 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study found that the COVID-19 pandemic has been a stressful period for nurses and HCAs in general practice, aligning with international accounts of primary care 25 27 29 35–37 39 56–58 and nurses’ experiences in general. 26 28 30–34 40 59–62 The necessity for meaningful and accessible short-term and long-term mental health support and continuous education and training are key recommendations in the literature. 21–23 25 28 31 32 37 38 40 57 59 However, this study emphasised additional measures that could help to better support primary care nurses, HCAs and the wider primary care team.…”
Section: Discussionmentioning
confidence: 99%
“…This feeling is emphasised by nurses in other qualitative studies from the pandemic, who also describe fear intensified by the tenuous nature of PPE—of inadequate quantity (as described in this study) but additionally of uncertain quality. 26 28 30–32 37–39 Literature from this pandemic and previous disease outbreaks suggests that the frontline nature of their role may place nurses at higher risk of physical and psychological distress than other healthcare professions. 26 32 33 Ensuring consistency in the quality and provision of PPE is critical to allow nurses to continue patient-facing activities confidently and safely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations